2010
DOI: 10.1007/s11104-010-0529-5
|View full text |Cite
|
Sign up to set email alerts
|

Brassica juncea seed meal particle size influences chemistry but not soil biology-based suppression of individual agents inciting apple replant disease

Abstract: Apple replant disease is incited by a pathogen complex composed of multiple fungal, oomycete and nematode species. Rhizoctonia solani AG-5 can be a significant component of this complex and is effectively suppressed via multiple functional mechanisms in response to Brassica juncea seed meal (SM) amendment. These mechanisms include those of both a biological and chemical nature. The effect of seed meal particle size on the operation of these mechanisms and the resulting capacity of B. juncea SM to suppress R. s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…The major bioactive compounds associated with mustard and other brassicaceous plants are isothiocyanates, the hydrolysis products of glucosinolates (Gimsing & Kirkegaard, 2006). Past work has shown that majority of isothiocyanate emissions, including allyl isothiocyanate, occurs within 24-72 h following addition to the soil system (Mazzola et al, 2007;Mazzola & Zhao, 2010). Isothiocyanates are thought to be effective in suppressing fungal pathogens, such as Rhizoctonia solani, during this relatively short window of time; however, soils amended with mustard seed meal still harbor the ability to suppress Rhizoctonia after 4 weeks of incubation (Mazzola et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major bioactive compounds associated with mustard and other brassicaceous plants are isothiocyanates, the hydrolysis products of glucosinolates (Gimsing & Kirkegaard, 2006). Past work has shown that majority of isothiocyanate emissions, including allyl isothiocyanate, occurs within 24-72 h following addition to the soil system (Mazzola et al, 2007;Mazzola & Zhao, 2010). Isothiocyanates are thought to be effective in suppressing fungal pathogens, such as Rhizoctonia solani, during this relatively short window of time; however, soils amended with mustard seed meal still harbor the ability to suppress Rhizoctonia after 4 weeks of incubation (Mazzola et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been shown that isothiocyanates degrade rapidly in the environment (i.e. > 99% of emissions occur within 24-72 h) (Mazzola et al, 2007;Mazzola & Zhao, 2010), soils amended with brassicaceous plant materials often retain the ability to suppress weeds and patho-gens for much longer periods of time, up to several weeks postamendment (Mazzola et al, 2007;Rice et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless the conversion rate detected in that study was still low (303 µmol glucosinolates/g seed meal, 3 mg seed meal/g soil applied = 909 nmol glucosinolates/g soil applied; = conversion rate of 7.7%). However, it has to be kept in mind that in that study, only the head space above the treated soil was sampled and not the soil itself [69]. Further, waterlogging to enhance isothiocyanate release [62] and soil tarping with plastic foils to keep the volatile compounds in the soil [67] are recommended.…”
Section: Biofumigationmentioning
confidence: 99%
“…This appeared to be largely due to greater fungal biomass in the mustard and sorghum-sudangrass treatments. For the mustard, this is especially interesting given the number of studies documenting its adverse effects on various soil fungi [11,15,16]. Our initial presumption was that the mustard would broadly inhibit soil fungal populations.…”
Section: Soil Microbial Communitiesmentioning
confidence: 99%
“…These compounds have been documented to have broad biocidal effects and suppress a number of soil pathogens, insects, and weeds [11][12][13][14]. Although numerous studies have documented the beneficial usage of brassicaceous plants or green tissue as biofumigants, only a limited number of studies have been conducted on use of brassicaceous oilseed meals for this purpose [11,[15][16][17]. Additionally, although the impacts of isothiocyanates and related compounds on microbial pathogens have been well documented, the impacts of nonpathogenic, soil microorganisms are largely unknown.…”
Section: Introductionmentioning
confidence: 99%